Analisis Sentimen dan Evolusi Topik terhadap Program Makan Bergizi Gratis Menggunakan IndoBERT dan cDTM - Muhammad Hamzah Fauzi; Ronsen Purba (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze public sentiment and the development of discussion topics related to the MBG program. Sentiment analysis was conducted using the IndoBERT model, while evolution topic analysis used the Continuous-Time Dynamic Topic Model (cDTM). The evaluation results showed that the IndoBERT model was able to classify sentiment with an accuracy value of 92.5% and an F1-score of 0.924. Integration between IndoBERT and cDTM showed a dominance of negative sentiment, especially in topics related to program implementation, while positive sentiment appeared more often in topics related to health and nutrition. The integration of sentiment and temporal topic analysis provides a more comprehensive understanding of the dynamics of public opinion regarding the MBG program.